Food Waste Co-Digestion with Microwave Pre-Treated Sewage Sludge to Enhance Biogas Production Through Anaerobic Digestion - Palanisamy K.; David H.; Muthaiyah G. (IEEE Computer Society, 2023)
Biodegradability; Biomass; Energy policy; Fossil fuels; Land fill; Methane; Municipal solid waste; Planning; Population statistics; Renewable energy resources; Sewage sludge; Sewage treatment plants; Sludge digestion; Sustainable development; Waste management; Biogas production; Environmental issues; Pretreatment methods; Renewable energies; Renewable energy source; Sustainable management; Waste handling; Waste recoveries; Anaerobic digestion